Firqam Enterprise: traditional food in Malaysia / Muhammad Faiz Izzuddin Abu Hassan ...[et al.] - Abu Hassan, Muhammad Faiz Izzuddin; Mohd Amran Johari, Qurratu' Aini; Raja Elias, Raja Nur Aqilah; Ishak, Fatihanum; Mohamad, Marina; Ayub, Fatin Aqila (2014)
The local food movement is now spreading globally, yet is not well understood. To many, local food is exclusively about proximity, with discriminating consumers demanding higher quality food grown, caught, processed, cooked, and sold by people they know and trust. But an equality important part of local food is local ownership of food businesses. This is about the full range of locally owned businesses involved in food, even though we are small food enterprise businesses; we are primary producers, manufacturers and retailers. Our focus is local and global markets in near future.